تحليل مسرحية "مغامرة رأس المملوك جابر " وفق نظرية الفعل الكلامي - فتينه لادا عدنان (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
يهدف هذا البحث إلى دراسة مسرحية "مغامرة رأس المملوك جابر "وفق نظرية الفعل الكلامي، هذه النظرية التي تُعنى بدراسة المعنى الذي تعدّه هو الاستعمال ، فهناك عبارات إذا نطقت بها لا تنشئ قولاً فحسب بل تؤدي فعلاً في الوقت نفسه ، وهذا ما سنركّز عليه في تحليل هذه المسرحية للكاتب سعد الله ونّوس التي حاولت قدر الإمكان دراستها دراسة وافية وفقاً لهذه النظرية ، وتقسيم الأفعال فيها حسب حقولها الدلالية . This research aims to study the play of " The adventure of Al –Mamlouk Gabers head " according to the theory of verbal verb . This theory which cares to study the meaning that considers it the use . There are clauses if you speak them ,they don’t give just word ,but they give actions at the same time ,and this what we are going to concentrate on in analyzing Saad ALah Wanous play . In this play I tried to study it as possible as I could according to this theory and dividing the verbs in it according to their indicative fields .